An analysis of the long run comovements between financial system development and mining production in South Africa - Ajagbe, Stephen Mayowa (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
This study examines the nature of the relationship which exists between mining sector production and development of the financial systems in South Africa. This is particularly important in that the mining sector is considered to be one of the major contributors to the country's overall economic growth. South Africa is also considered to have a very well developed financial system, to the point where the dominance of one over the other is difficult to identify. Therefore offering insight into the nature of this relationship will assist policy makers in identifying the most effective policies in order to ensure that the developments within the financial systems impact appropriately on the mining sector, and ultimately on the economy. In addition to using the conventional proxies of financial system development, this study utilises the principal component analysis (PCA) to construct an index for the entire financial system. The multivariate cointegration approach as proposed by Johansen (1988) and Johansen and Juselius (1990) was then used to estimate the relationship between the development of the financial systems and the mining sector production for the period 1988-2008. The study reveals mixed results for different measures of financial system development. Those involving the banking system show that a negative relationship exists between total mining production and total credit extended to the private sector, while liquid liabilities has a positive relationship. Similarly, with the stock market system, mixed results are also obtained which reveal a negative relationship between total mining production and stock market capitalisation, while a positive relationship is found with secondary market turnover. Of all the financial system variables, only that of stock market capitalisation was found to be significant. The result with the financial development index reveals that a significant negative relationship exists between financial system development and total mining sector production. Results on the other variables controlled in the estimation show that positive and significant relationships exist between total mining production and both nominal exchange rate and political stability respectively. Increased mining production therefore takes place in periods of appreciating exchange rates, and similarly in the post-apartheid era. On the other hand, negative relationships were found for both trade openness and inflation control variables. The impulse response and variance decomposition analyses showed that total mining production explains the largest amount of shocks within itself. Overall, the study reveals that the mining sector might not have benefited much from the development in the South African financial system.
Keywords: Economic development -- South Africa; Econometric models; Mineral industries -- Economic aspects -- South Africa; South Africa -- Economic conditions; South Africa -- Economic policy; Principal components analysis; Cointegration; Stock exchanges -- South Africa; Banks and banking -- South Africa; Foreign exchange rates